2022
DOI: 10.2174/0929867328666210810152917
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based Design of Anti-cancer Vaccines: The Significance of Antigen Presentation to Boost the Immune Response

Abstract: : Immunotherapy, alone or in combination with other therapies, is widely used against cancer. Glycoprotein Mucin 1 (MUC1), which is overexpressed and aberrantly glycosylated in tumor cells, is one of the most promising candidates to engineer new cancer vaccines. In this context, the development of stable antigens that can elicit a robust immune response is mandatory. Here, we describe the design and in vivo biological evaluation of three vaccine candidates based on MUC1 glycopeptides that comprise unnatural el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…A very recent study by the Corzana group reported on the preparation of various vaccines made up of the MUC1/Tn antigen epitope and showed that conformational restriction using a Thr or other unnatural amino acids and/or sugar analogues that maintained a restricted presentation elicited higher antibody titers and bound more efficiently to tumor cells that are known to display that structure. (Asin et al, 2022). This would be considered precisely what was described above: Certain structures must mimic the cell surface presentation much better than others.…”
Section: Discussionmentioning
confidence: 77%
“…A very recent study by the Corzana group reported on the preparation of various vaccines made up of the MUC1/Tn antigen epitope and showed that conformational restriction using a Thr or other unnatural amino acids and/or sugar analogues that maintained a restricted presentation elicited higher antibody titers and bound more efficiently to tumor cells that are known to display that structure. (Asin et al, 2022). This would be considered precisely what was described above: Certain structures must mimic the cell surface presentation much better than others.…”
Section: Discussionmentioning
confidence: 77%
“…On the one hand, the administration of glycan-based therapies has been suggested for anticancer vaccination. 41,42 On the other hand, recognition of Tn-positive tumor cells by immune cells may result in immunosuppression, 43,44 by promoting Treg cell differentiation and favoring suppression of T cell activation. Exogenously administered purified MGL could thus be used to compete and reduce the binding of dendritic cells on the Tn-expressing tumor cells, and thus reducing tumor escape.…”
Section: ■ Discussionmentioning
confidence: 99%
“…[69][70] Francisco Corzana et al made a number of chemical modifications to tumor vaccines based on MUC1. [71] They constructed an α-methylserine Tn antigenic variant (MeSer) [72] that was integrated into the most immunogenic PDTRP fragment of MUC1 (Figure 3E). Although this non-natural glycopeptide exhibited good stability in the blood, there was no significant difference in terms of enhancement of antigen immunogenicity compared with natural glycopeptides, perhaps because the additional flexibility of unnatural amino acids was adversely affected.…”
Section: Modification Of Glycopeptide Antigen Itselfmentioning
confidence: 99%